Effects of school‐based interventions for direct delivery of physical activity on fitness and cardiometabolic markers in children and adolescents: a systematic review of randomized controlled trials. Issue 10 (4th June 2013) - Sun, C.; Pezic, A.; Tikellis, G.; Ponsonby, A‐L.; Wake, M.; Carlin, J. B.; Cleland, V.; Dwyer, T.
Summary To evaluate the effectiveness of school‐based physical activity interventions on fitness, adiposity and cardiometabolic outcomes among schoolchildren. Medline, Embase, EBSCOhost CINAHL and ERIC databases were searched up to October 2012. Inclusion criteria: intervention delivered at school with controls having no intervention or usual physical education classes; participants aged 5–18 years; outcomes spanning some or all of the above. We assessed levels of evidence for identified trials based on methodological quality and sample size. Dose of the interventions (a total summary measure of intensity, frequency and duration) were considered. Eighteen randomized controlled trials (RCTs, total participants = 6, 207) were included, of which six were large, higher quality trials with high dose of the intervention. The intervention was consistent in increasing fitness with large, higher quality studies and high dose of intervention providing strong evidence. Dose of school‐based physical activity is an important determinant of trial efficiency. Some large, higher quality RCTs provided strong evidence for interventions to decrease skin‐fold thickness, increase fitness and high‐density lipoprotein cholesterol. Evidence for body mass index, body fat and waist circumference, blood pressure and triglycerides, low‐density lipoprotein cholesterol and total cholesterol remain inconclusive and require additional higher quality studies with high dose of interventions to provide conclusive evidence.